Penerapan Problem Solving Berorientasi Kontekstual Untuk Meningkatkan Komunikasi Dan Hasil Belajar Matematika Siswa Madrasah Tsanawiyah - Imawati, Soffana (Jurnal VARIDIKA, 2020)
In general, this study aims to improve communication and learning outcomes in mathematics with contextual oriented learning problem solving for students of MTs Negeri 1 Pemalang, Central Java. Specifically, it aims (1) to describe the improvement of mathematical communication with contextual-oriented problem solving learning for MTs students, and (2) describe the improvement of mathematics learning outcomes by contextual-oriented learning problem solving for MTs students. This class action research was conducted in 8.3 MTs Negeri 1 Pemalang class. Data sources, teachers and students. Data were collected by observation, field notes, documentation, and tests. Source and method triangulation is used for data validity. Analysis technique with constant comparison. The results of the study, in general contextual oriented problem solving learning can improve communication and mathematics learning outcomes of MTs students. Learning with contextual-oriented problem solving can improve communication and learning mathematics. Improved communication was observed from four indicators. The ability to speak until the second cycle is 62.86%. The ability to draw until cycle II is 68.57%. The ability to write until the second cycle is 74.29%. The ability to explain the concept until the second cycle is 65.71%. Learning with contextual-oriented problem solving can improve mathematics learning outcomes. Improved mathematics learning outcomes measured by the number of students who complete. The number of students who completed this study up to cycle II was 74.29%.Â